Constructability Factors in the Malaysian Construction Industry - Nima, Mekdam A. (2001)
Advances have been made in the theory and implementation of constructability in many developed countries such as the United States, United Kingdom and Australia. This is not observed in the Malaysian construction industry. This research aimed to narrow this gap. The first objective of this study is to establish statistical models to describe constructability implementation in the Malaysian construction industry so that an insight on the factors contributing to the constructability implementation can be established. The second objective is to evaluate the independent factors affecting constructability implementation in the Malaysian construction industry. The research findings were based on an industry wide questionnaire survey and four case studies: two highways projects, a cable stayed bridge and a sport complex. These case studies underpinned the results of the survey. A series of logistic predictive models were developed to assist managers in predicting the probabilities of successful implementation of the constructability concepts in their organizations, based on the estimates and the odds ratios of the independent factors. This provides a quantitative approach to constructability implementation in the Malaysian construction industry. The study reveals that five out of the eight examined factors significantly (p<O.50) affect constructability implementation. These are organization type, level of education, design experience, construction experience and engineers' attitude. The five significant factors can be used to enhance the Malaysian construction industry. The first significant factor of education level is more difficult to control than the other factors. The second and third significant factors of design experience and construction experience can be controlled through acquiring of knowledge and better access to information. The fourth significant factor of the engineers' attitude towards constructability implementation can be enhanced through publishing constructability guides. The fifth significant factor of organization type entails targeting engineers in client and consultant organizations more than the engineers in contracting and construction management organizations.